Eco-efficiency Modeling in the Production of Alcohol Based on Data Envelopment Analysis - Danastri Ratna Nursinta Dewi; Singgih Saptadi; Heru Prastawa (School of Postgraduate Studies, Diponegoro Univer, 2022)
Economic growth can be assessed through industrial development. However, problems arise regarding the discharge of waste into lakes or rivers, leading to biodiversity loss and endangering human health. A study conducted in the UK stated that small and medium enterprises (SMEs) were the largest contributor to waste and pollution. This was because they ignored the regulations governing environmental management. As happened in the Bekonang alcohol industry center, the waste from the alcohol production process polluted the Bengawan Solo tributary as the Water Supply Corporation (WSC). In order to overcome these problems, we need a measurement that can increase production efficiency. Eco-efficiency is a concept that combines efficiency and economy based on efficiency principles. The different models are proposed to measure the eco-efficiency of production, namely with a weighting system that aggregates environmental results. The Data Envelopment Analysis (DEA) enables aggregation without the need for subjective or normative judgments about weights. Although DEA does not require subjective or normative judgments, weight restrictions can be incorporated into the framework. The purpose of this study was to determine the eco-efficiency of the Bekonang alcohol production process using the economic results of the production process and the environmental impact assessed through a life cycle assessment (LCA). There were three products, namely 30% alcohol for consumption, 90% alcohol for medical purposes, and hand sanitizer. The environmental impact was assessed from a life cycle assessment, while the economic assessment was determined by calculating the net profit for each product at a capacity of 100 liters/day. Economic assessment can be divided into two perspectives, namely the Social Perspective (SP) and Company Perspective (CP). From the modeling results, the most eco-efficient production process was hand sanitizer with an eco-efficiency value of 1.ABSTRAKPertumbuhan ekonomi dapat dinilai melalui perkembangan industri, tetapi masalah muncul terkait pembuangan limbah ke danau atau sungai yang menyebabkan hilangnya keanekaragaman hayati yang membahayakan kesehatan manusia. Penelitian yang dilakukan di Inggris menyatakan, jika penyumbang limbah dan polusi terbesar adalah dari usaha kecil menengah (UKM), karena mereka mengabaikan peraturan yang mengatur tentang pengelolaan lingkungan. Seperti yang terjadi di sentra industri alkohol Bekonang, limbah hasil proses produksi alkohol mencemari anak sungai Bengawan Solo sebagai suplai air PDAM. Untuk mengatasi masalah tersebut diperlukan suatu pengukuran yang dapat meningkatkan efisiensi produksi. Eko-efisiensi merupakan konsep yang menggabungkan efisiensi dan ekonomi berdasarkan prinsip efisiensi. Model yang berbeda diusulkan untuk mengukur eko-efisiensi pada suatu produksi, yaitu dengan sistem pembobotan yang mengagregasi hasil lingkungan. Analisis data envelopment analysis (DEA) memungkinkan agregasi tanpa membutuhkan penilaian subjektif atau normatif pada bobot. Meskipun DEA tidak memerlukan penilaian subjektif atau normatif, pembatasan bobot dapat dimasukkan ke dalam kerangka kerja. Tujuan dari penelitian ini adalah untuk mengetahui nilai eko-efisiensi proses produksi alkohol Bekonang, menggunakan hasil ekonomi dari proses produksi dan dampak lingkungan, yang dinilai melalui life cycle assessment (LCA).Terdapat tiga produk yang dianalisi, alkohol 30% untuk konsumsi; alkohol 90% untuk keperluan medis; dan hand sanitizer. Dari hasil pemodelan yang telah dilakukan, proses produksi yang paling eko-efisien adalah hand sanitizer dengan nilai eko-efisiensi adalah 1.